Cak Lontong's Humorous Discourse on Youtube Media in Pragmatic Perspective - Rohmadi, Muhammad; Fauzi, Aziz; Hubi, Zindan Baynal; Pratama, Aditya (Universitas Muhammadiyah Malang, 2023)
This study discusses the use of various speech acts in humorous discourse used by Cak Lontong on YouTube media from a pragmatic perspective. Humor can be used to convey multiple intentions that are described in a more relaxed and entertaining manner. Speakers and partners must understand the uniqueness of humorous speech so that the meaning of the speech can be adequately understood. This study used the qualitative descriptive method. The data source used is a document in the form of Cak Lontong's humorous speech in the Cak Lontong YouTube video. The data used in this study is the humorous speech of Cak Lontong, which entertains the opponent or audience. The focus of this research is to: (1) explain the function of speech acts; (2) explain the maxim of cooperation and violations of the maxim of cooperation; and (3) describe the use of direct and indirect speech acts. Based on the analysis and discussion results, it can be concluded that Cak Lontong uses assertive, rescriptive, expressive, and declarative speech acts to create humor. In addition, the speech delivered also contains direct and indirect speech and violates the principle of cooperation to create humor for the interlocutor or audience. The power of communication is in the speech process. The construction of meaning that the speaker can translate well will make the speech more interesting. The pragmatic approach is an alternative concept for speakers and co-speakers in constructive communicative activities. This study used a pragmatic approach to describe and explain the various speech acts used by Cak Lontong with humor. Various discussions by researchers about the maxim of politeness, the function of speech acts, direct speech acts, and indirect speech acts were an effort to describe the various speech acts of Cak Lontong in various contexts of speech. Different discussions are expected to provide theoretical implications regarding the pragmatic approach in Cak Lontong's humorous discourse.